2006
DOI: 10.1039/b601513c
|View full text |Cite
|
Sign up to set email alerts
|

High field ENDOR as a characterization tool for functional sites in microporous materials

Abstract: The determination of the details of the spatial and electronic structure of functional sites (centers) in any system, be it in materials chemistry or in biology, is the first step towards understanding their function. When such sites happen to be paramagnetic in any point of their activity cycle, the tool box offered by a variety of high resolution electron paramagnetic resonance (EPR) spectroscopic techniques becomes very attractive for their characterization. This tool box has been considerably expanded by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 131 publications
(234 reference statements)
0
21
0
Order By: Relevance
“…In the last decade numerous applications of high field CW EPR and ENDOR have been reported and the virtues of measurements at a high field have been well demonstrated and established [1][2][3][4][5][6]. Recently, it has also been demonstrated that distance measurements between paramagnetic centers by pulsed DEER techniques can also be performed at high fields [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the last decade numerous applications of high field CW EPR and ENDOR have been reported and the virtues of measurements at a high field have been well demonstrated and established [1][2][3][4][5][6]. Recently, it has also been demonstrated that distance measurements between paramagnetic centers by pulsed DEER techniques can also be performed at high fields [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…In the past, due to widespread use of proton related ESEEM measurements it was often assumed that ESEEM spectroscopy is best performed at low frequencies (2)(3)(4)(5)(6)(7)(8)(9) to decrease Zeeman frequencies of nuclei and therefore facilitate the simultaneous excitation of forbidden and allowed EPR transitions necessary for the generation of the ESEEM effect. This led to the design and construction of low frequency pulse EPR spectrometers such as S-and C-band spectrometers [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A review on the advantages of high field ENDOR in the characterization of functional sites in microporous materials can be found in Ref. [9], while some case studies are reported in ref [10][11][12][13]. Even though the application of these techniques is limited to cryogenic temperatures and, at present, not applicable under operando conditions, socalled hyperfine spectroscopy (ESEEM, ENDOR, HYSCORE) allows monitoring the distribution of the unpaired electrons wave function, which is one of the most useful of the molecular ''fingerprints'' obtained from an EPR spectrum, over first and second coordinative shells.…”
Section: Introductionmentioning
confidence: 99%
“…It was first observed over a half century ago and has been particularly useful in characterizing organic radicals, metal complexes, and biomolecules with paramagnetic centers (Brückner, 2010; Goldfarb, 2006). However, with the development of site-directed spin-labeling (SDSL) techniques to target biological systems, there has been a significant increase in the application of EPR spectroscopy to study protein structure and dynamics (Alexander, Bortolus, Al-Mestarihi, Mchaourab, & Meiler, 2008; Altenbach, Flitsch, Khorana, & Hubbell, 1989; Fanucci & Cafiso, 2006; Hirst, Alexander, McHaourab, & Meiler, 2011; Hubbell, Gross, Langen, & Lietzow, 1998; Hubbell, López, Altenbach, & Yang, 2013; Sahu, McCarrick, & Lorigan, 2013; Sahu, McCarrick, Troxel, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%